The effect of different bone level and prosthetic connection on the biomechanical response of unitary implants: Strain gauge and finite element analyses - Datte, Carlos Eduardo; Rodrigues, Vinícius Anéas; Datte, Fabiana Barbi; Scalzer Lopes, Guilherme da Rocha; Borges, Alexandre Luiz Souto; Nishioka, Renato Sussumu (International Journal of Advanced Engineering Research and Science, 2021)
Different prosthetic connections have emerged for better aesthetic and biomechanical performance to prevent peri-implant bone loss. The finite elements analysis and the strain gauge methodologies were used for the numerical analysis of the generated stress and the microstrain around the implants and their connections. Two implant models with the same length (13 x 3.75 mm) were analyzed according to the prosthetic connection: external hexagon or morse Taper. Both abutments received screw-retained metallic crowns in chromium-cobalt. The peri-implant tissue was simulated using polyurethane resin in two different heights (bone level and 5 mm of bone loss). A load of 300 N was applied on the occlusal surface. The results were analyzed in terms of von-Mises stress and micro strain. Samples identical to the numerical models were made for the Strain Gauge (SG) analysis; four SGs were bonded around the implant to obtain micro strain results. Finite element analysis and strain gauge corroborated in terms of similar mechanical response. Thus, there is no difference regarding the prosthetic connection for the generated stress and strain under axial load. However, bone loss increased the stress and strain magnitude for both prosthetic connections. In conclusion, both evaluated implant connections present similar biomechanical behavior regardless the bone height.